Review paperCommunity health case studies selected from developing and developed countries – common principles for moving from evidence to action - White, Franklin; Nanan, Debra (Archives of Medical Science, 2008)
Community health is an effective strategy when it uses evidence to identify needs, resources and opportunities to assist communities to enhance their health status. To respond to community needs requires a commitment to population health research and evaluation, and to partnerships committed to a participative approach. Community health initiatives selected for this review reveal to varying degrees the incorporation of health goals within broader public agendas, collaboration of government with private and voluntary sectors, encouragement of coalitions, integrated approaches, and commitment to evaluation of processes and outcomes. Underlying these initiatives were found strong elements of broad strategic thinking: social development, healthy public policy, health systems development. Each required leadership within a distinct context, and can be defended as a public health priority. They all followed an evidence-based approach to planning: Where are we? Where do we want to be? How are we going to get there? How will we know we are getting there? Community participation was a key success factor. Community health initiatives must be scientifically sound, culturally acceptable, and managerially feasible. Evidence is not enough to generate action; leadership is essential: “the capacity to influence others to work together to achieve a common purpose”.